Religious and philosophic context of traditional outlook of Kazakhs - Baydarov, Erkin U. (The New Research of Tuva, 2012)
Article reviews the religious and philosophical context of traditional outlook of Kazakhs which reflects the treasures of their national culture and their learning styles through a prism of Tengriism.